Securing e-learning: challenges and solutions for cybersecurity in higher education - Mokhtar, Norashikin; Ismail, Mohd Faiz; Nik Mat, Nik Mahfuzah; Ahmad, Irma (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The digital revolution has profoundly impacted education by enabling flexible, personalised, and convenient learning through e-learning platforms. However, this transformation has also led to a significant rise in cybersecurity threats, which higher education institutions must urgently address (Sadiqzade & Alisoy, 2025). Advancements in technology have enabled learning materials to transition from physical classrooms to online spaces, opening access and facilitating collaborative engagement among universities. However, such a shift also carries substantial operational risks. While students and teachers begin to use more digital tools, they are also exposing themselves to threats, including hacking, phishing, ransomware, and unauthorised access.